Anxiety and Depression Among College Students During the COVID-19 Lockdown: A Cross-Sectional Survey in Jiangsu, China - Qin B; Hu Z; Liu W; Sun Y; Wang Y; Zhang H; Yang F; He Y (Dove Medical Press, 2023)
Banghui Qin,1,2,* Zhiqing Hu,1,2,* Wuqianhui Liu,3,* Yanjun Sun,1,2 Yiping Wang,4 Huiying Zhang,1,2 Fan Yang,5 Yuan He1,2 1Institute of Medical Humanities, Nanjing Medical University, Nanjing, 211166, People's Republic of China; 2School of Marxism, Nanjing Medical University, Nanjing, 211166, People's Republic of China; 3The First School of Clinical Medicine, Nanjing Medical University, Nanjing, 211166, People's Republic of China; 4School of Nursing, Nanjing Medical University, Nanjing, 211166, People's Republic of China; 5School of Education Science, Jiangsu Normal University, Xuzhou, 221116, People's Republic of China*These authors contributed equally to this workCorrespondence: Yuan He; Fan Yang, Tel +86 18651625286 ; +86 18936356069, Email heyuan@njmu.edu.cn; 6020050038@jsnu.edu.cnBackground: This study aimed to explore the levels of anxiety and depression in a sample of home-quarantined college students to identify the risk factors for psychological distress during the COVID-19 lockdown.Methods: A total of 1156 college students studying in Jiangsu, China, participated from August 5 to August 14. A structured questionnaire was used to collect data anonymously, including demographic characteristics, the generalized anxiety disorder-7 (GAD-7) questionnaire, the patient health questionnaire-9 (PHQ-9), a physical activity scale, and items related to COVID-19. The chi-square test and Fisher's exact test were employed to establish the differences in levels of anxiety and depression across sociodemographic characteristics. Binary logistic regression was applied to measure the predictors of levels of anxiety and depression, and associations were considered significant at p < 0.05.Results: The estimates of anxiety and depression were 48.1% and 57.6%, respectively. The univariate analysis indicated a significant difference in anxiety levels across student grades, whether the student was an only child, the distance from the worst-hit areas, and physical activity/exercise intensity. Physical activity intensity and living in communities with infected people were statistically correlated with the level of depression. Binary logistic regression results indicated that the predictive factors for anxiety were living within a short distance from the worst-hit areas (10~20 km), engaging in higher education (graduate students), and low-intensity daily exercise. Factors statistically predicting depression symptoms were having siblings, a COVID-19 diagnosis in the community and low-intensity daily exercise.Conclusion: During outbreaks, students in an extremely stressful state are more likely to develop anxiety and depression, particularly postgraduates. Psychological interventions to reduce fears and encourage exercise should be available to home-quarantined college students. Students who live in the worst-hit areas and are not the only child in the family should be prioritized.Keywords: coronavirus disease 2019, college students, mental health, depression, anxiety, fears